Etiology and complications of acute gastroenteritis in hospitalized children - Nardin Elias; Daniela Pop (Amaltea Medical Publishing House, 2022)
Diarrheal diseases represent a leading cause of morbidity and mortality in children less than 5 years of age. The aim of our study was to examine the most common etiologies and complications of acute gastroenteritis (AGE) in children hospitalized in our clinic, in different seasons. Material and method. We retrospectively evaluated the data of 199 children [mean value of the age ± standard deviation (SD)=2.45±2.5years] admitted in one year in our department and diagnosed with AGE. Results. Rotavirus was found in 15.6% (31/199) of the patients; adenovirus in 9.5% (19/199). Rotavirus was found to be the dominating confirmed pathogen in most of the months, throughout the year. The duration of the symptoms from the onset of the disease until discharge ranged between 2-21 days, mean value ± SD=5.2±2.69 days. More than half of the patients had signs of moderate dehydration (53.3%-106/199 patients) and 39.6% (79/199) signs of mild dehydration. Conclusions. In our study, AGE affected children between 1-5 years of age primarily. Rotavirus was the leading etiology found in most pediatric age groups. Severe complications in children with AGE and no other chronic diseases were rare.